Precoding design for interference suppression in multi-cell multi-user networks - Liu, Heng; Ding, Zhiguo; Fan, Pingzhi; Hao, Li (IET communications, 2014)
This study focuses on the design of downlink transmission protocols in multi-cell multi-user mobile networks, where co-channel interference has been recognised as a challenging issue particularly for the users close to the boundary of cells. The key idea of this study is to jointly apply interference alignment (IA) and pre-cancellation to the addressed scenario, where the former technique can effectively increase the overall system throughput and the latter can significantly boost the diversity gains and reception reliability. To ensure the diversity gains can be achieved with zero-forcing IA, a precoder optimisation scheme is proposed based on the well-known iterative interference leakage minimisation scheme. Both analytic and numerical results have been developed to show the capacity and diversity gains obtained by using the proposed scheme. Besides, the computational complexity of the proposed scheme and the effects of imperfect channel state information on the performance are studied as well.